Patient Experiences of Psilocybin-Assisted Psychotherapy: An Interpretative Phenomenological Analysis. (July 2017) - Belser, Alexander B.; Agin-Liebes, Gabrielle; Swift, T. Cody; Terrana, Sara; Devenot, Neşe; Friedman, Harris L.; Guss, Jeffrey; Bossis, Anthony; Ross, Stephen
The psychological mechanisms of action involved in psilocybin-assisted psychotherapy are not yet well understood. Despite a resurgence of quantitative research regarding psilocybin, the current study is the first qualitative study of participant experiences in psilocybin-assisted psychotherapy. Semistructured interviews were carried out with 13 adult participants aged 22 to 69 years ( M = 50 years) with clinically elevated anxiety associated with a cancer diagnosis. Participants received a moderate dose of psilocybin and adjunctive psychotherapy with an emphasis on the process of meaning-making. Verbatim transcribed interviews were analyzed by a five-member research team using interpretative phenomenological analysis. General themes found in all or nearly all transcripts included relational embeddedness, emotional range, the role of music as conveyor of experience, meaningful visual phenomena, wisdom lessons, revised life priorities, and a desire to repeat the psilocybin experience. Typical themes found in the majority of transcripts included the following: exalted feelings of joy, bliss, and love; embodiment; ineffability; alterations to identity; a movement from feelings of separateness to interconnectedness; experiences of transient psychological distress; the appearance of loved ones as guiding spirits; and sharing the experience with loved ones posttreatment. Variant themes found in a minority of participant transcripts include lasting changes to sense of identity, synesthesia experiences, catharsis of powerful emotion, improved relationships after treatment, surrender or "letting go, " forgiveness, and a continued struggle to integrate experience. The findings support the conclusion that psilocybin-assisted psychotherapy may provide an effective treatment for psychological distress in cancer patients. Implications for theory and treatment are discussed.